2020
DOI: 10.1021/acs.energyfuels.9b04192
|View full text |Cite
|
Sign up to set email alerts
|

Pore Characterization and Inner Adsorption Mechanism Investigation for Methane in Organic and Inorganic Matters of Shale

Abstract: The pore characterization and the adsorption property for gas shale have been studied widely due to the vigorous exploration of shale gas reservoirs. However, for a particular shale sample, few research studies have focused on the pore characterizations and inner adsorption mechanisms for different types of pores in organic and inorganic matters. In this research, a low-pressure N 2 /CO 2 adsorption method with a novel analysis and a simplified local density (SLD) method with a particular regression were utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 62 publications
2
15
0
Order By: Relevance
“…Moreover, the kerogen pore surface is not smooth, carrying varying degrees of surface roughness. Kuila and Prasad recommended the use of consistency criteria proposed by Rouquerol et al Moreover, as the BET model only provides qualitative estimation of surface area, it should be used with cautions for quantitative computation of the average pore diameter , by combining the BET surface area and total pore volume.…”
Section: Characterization Of Pore Size Distribution and Specific Surf...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the kerogen pore surface is not smooth, carrying varying degrees of surface roughness. Kuila and Prasad recommended the use of consistency criteria proposed by Rouquerol et al Moreover, as the BET model only provides qualitative estimation of surface area, it should be used with cautions for quantitative computation of the average pore diameter , by combining the BET surface area and total pore volume.…”
Section: Characterization Of Pore Size Distribution and Specific Surf...mentioning
confidence: 99%
“…58 The geophysical properties of shale rocks have been generally characterized by total organic carbon (TOC) analysis, 59−61 rock-eval pyrolysis, 62−65 and X-ray diffraction (XRD) experiments 66−69 to determine the TOC content, thermal maturity, and chemical compositions. Generally, the adsorbed methane amount has a positive correlation with the TOC content in shale samples, 23,70,71 while clay minerals can also significantly contribute to shale gas adsorption. 23 In addition, experimental studies have reported that methane adsorption in shale significantly decreases due to the presence of moisture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shale samples analyzed in this study were collected from the Upper Ordovician Wufeng Formation (O 3 w) and the Lower Silurian Longmaxi Formation (S 1 l) in Sichuan Basin. The Upper Ordovician Wufeng-Lower Silurian Longmaxi (O 3 w-S 1 l) shales are one of the most productive shale gas formations in China. The Upper Ordovician Wufeng Formation was deposited in a deep-water shelf sedimentary environment, which was a benefit for the preservation of organic matter. Kinds of graptolite fossil were identified from the shales of Wufeng Formation. , The Longmaxi Formation was deposited from a deep-water shelf to a shallow-water shelf environment.…”
Section: Sample and Experiments Proceduresmentioning
confidence: 99%
“…Spontaneous imbibition is related to the capillary rise of a wetting liquid. 14 Because of the extremely fine pore sizes, 15 the capillary pressures of the partially saturated shale matrix are very high, 16 causing fracturing water infiltration into the rock matrix. At the same time, the hydraulic fracturing operation creates a network of interconnected fractures that exposes a great surface area of the rock.…”
Section: Introductionmentioning
confidence: 99%